Analysis of the Influence of Self Congruity, Functional Congruity, Perceived Value, and Attractiveness of Alternatives on Customer Satisfaction and Ultimately Customer Loyalty at Hypermart Lippo Plaza in Kupang - Chrisantus Yobelto Seran (International Journal of Economics Accounting and Management, 2024)
The retail industry has experienced rapid growth and development throughout the world, including Indonesia. One of the major retail industries in Indonesia, namely Hypermart. Apart from providing jobs, Hypermart also contributed greatly to the growth of the national economy. Thus, making it one of the multipurpose stores that is quite reliable by the public, and Hypermart also really maintains consumer loyalty by continuously strengthening consumer satisfaction in using the products and services offered by Hypermart. The purpose of this study was to determine the effect of self-congruity, functional congruity, perceived value, attractiveness of alternatives and customer satisfaction on customer loyalty. The benefit of this research is to increase insight and knowledge, especially in knowing how much influence customer satisfaction has so that it can increase customer loyalty. This research is a causal research using quantitative methods and processed with the help of a statistical program, namely AMOS version 22.0. Data was collected by distributing questionnaires using the snowball sampling technique to 100 respondents, with the characteristics of the respondents being both male and female, aged 18-60 years, domiciled in Kupang, had bought and visited Hypermart at least 2 (two) times in the period within the last 6 (six) months, have purchased and used other similar products in the past year and have interacted with employees of Hypermart